2007
DOI: 10.1001/archpedi.161.10.986
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and Health Care Access After Emancipation

Abstract: Objective: To estimate the association between housing status and health care access and outcomes among young adults aging out of the child welfare system. Results: Among the 345 emancipated participants, 14.2% experienced homelessness and 39.4% were unstably housed. In multivariate analysis of emancipated participants, homelessness was associated with being uninsured (AOR, 3.41; 95% confidence interval, 1.52-7.63) and having unmet need for health care (AOR, 3.26; 95% confidence interval, 1.40-7.56); it was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…DHHS,, 2012). It is well documented that in comparison to the general population, young people with foster care experience are more likely to experience a variety of behavioral, physical, mental health, social, educational, and economic challenges (Ahrens, Richardson, Lozano, Fan, & DuBois, 2008; Carpenter, Clyman, Davidson, & Steiner, 2001; Courtney, Dworsky, Lee, & Raap, 2010; Courtney et al, 2005; Courtney, Terao, & Bost, 2004; Keller, Salazar, & Courtney, 2010; Kushel, Yen, Gee, & Courtney, 2007; McMillen et al, 2005; Merikangas et al, 2010; Narendorf & McMillen, 2010; Pecora et al, 2005; Pecora, White, Jackson, & Wiggins, 2009; Pecora et al, 2003; Pilowsky & Wu, 2006; Vaughn, Ollie, McMillen, Scott, & Munson, 2007; Zlotnick, Tam, & Soman, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…DHHS,, 2012). It is well documented that in comparison to the general population, young people with foster care experience are more likely to experience a variety of behavioral, physical, mental health, social, educational, and economic challenges (Ahrens, Richardson, Lozano, Fan, & DuBois, 2008; Carpenter, Clyman, Davidson, & Steiner, 2001; Courtney, Dworsky, Lee, & Raap, 2010; Courtney et al, 2005; Courtney, Terao, & Bost, 2004; Keller, Salazar, & Courtney, 2010; Kushel, Yen, Gee, & Courtney, 2007; McMillen et al, 2005; Merikangas et al, 2010; Narendorf & McMillen, 2010; Pecora et al, 2005; Pecora, White, Jackson, & Wiggins, 2009; Pecora et al, 2003; Pilowsky & Wu, 2006; Vaughn, Ollie, McMillen, Scott, & Munson, 2007; Zlotnick, Tam, & Soman, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Homeless young adults are at elevated risk for psychiatric disorders (1, 2), with affective and anxiety disorders nearly twice as likely compared to housed individuals around the same age (3, 4). Psychiatric disorders are associated with considerable impairment in functioning (5) that may impede the development of independent living skills and efforts to obtain and retain housing (6–8).…”
Section: Introductionmentioning
confidence: 99%
“…Emancipation occurs when adolescents leave protective custody, generally between ages 18 and 21, without a permanency arrangement (e.g., guardianship, adoption, reunification). Studies have demonstrated that young people emancipating from protective custody experience significantly higher rates of substance abuse, mental health concerns, and poorer quality of life when compared to their same-aged peers never in protective custody (Dworsky, Ahrens, & Courtney, 2013;Dworsky & Courtney, 2009a;Dworsky & Courtney, 2009b;Dworsky & Courtney, 2010;Fowler, Toro, & Miles, 2011;Kushel, Yen, Gee, & Courtney, 2007). Several mechanisms likely contribute to the increased risk for poor outcomes observed for young people who emancipate from protective custody.…”
mentioning
confidence: 99%